Revival of Leishmanization and Leishmanin - Pacheco-Fernandez, Thalia; Volpedo, Greta; Gannavaram, Sreenivas; Bhattacharya, Parna; Dey, Ranadhir; Satoskar, Abhay; Matlashewski, Greg; Nakhasi, Hira L. (Frontiers in Cellular and Infection Microbiology, 2021)
Leishmaniasis includes a spectrum of diseases ranging from debilitating cutaneous to fatal visceral infections. This disease is caused by the parasitic protozoa of the genus Leishmania that is transmitted by infected sandflies. Over 1 billion people are at risk of leishmaniasis with an annual incidence of over 2 million cases throughout tropical and subtropical regions in close to 100 countries. Leishmaniasis is the only human parasitic disease where vaccination has been successful through a procedure known as leishmanization that has been widely used for decades in the Middle East. Leishmanization involved intradermal inoculation of live Leishmania major parasites resulting in a skin lesion that following natural healing provided protective immunity to re-infection. Leishmanization is however no longer practiced due to safety and ethical concerns that the lesions at the site of inoculation that can last for months in some people. New genome editing technologies involving CRISPR has now made it possible to engineer safer attenuated strains of Leishmania, which induce protective immunity making way for a second generation leishmanization that can enter into human trials. A major consideration will be how the test the efficacy of a vaccine in the midst of the visceral leishmaniasis elimination program. One solution will be to use the leishmanin skin test (LST) that was also used for decades to determine exposure and immunity to Leishmania. The LST involves injection of antigen from Leishmania in the skin dermis resulting in a delayed type hypersensitivity (DTH) immune reaction associated with a Th1 immune response and protection against visceral leishmaniasis. Reintroduction of novel approaches for leishmanization and the leishmanin skin test can play a major role in eliminating leishmaniasis.